Pulsed Magnetic Field Treatment Effects on Undissolved Carbides in Continuous Casting Billets of GCr15 Bearing Steel - Lijuan Shen; Ruiqing Lang; Shuqing Xing; Yonglin Ma (Metals, 2024)
The study investigates the effect of pulsed magnetic fields on undissolved carbides in high-carbon chromium bearing steel GCr15 billets. The billets were subjected to heat treatment at 950 °C, with a pulsed magnetic field of varying durations applied during the process. The influence of the pulsed magnetic field on the distribution of undissolved carbides within the billets was investigated, and the thermodynamic and kinetic mechanisms of undissolved carbides dissolution were explored. The results indicate that the area percentage of undissolved carbides in the microstructure decreases from 1.68% to 0.06% after applying a pulsed magnetic field for 10 min, and the size of undissolved carbides decreases from 17.5 μm to 4.9 μm. When a pulsed magnetic field is applied for 30 min, all undissolved carbides dissolve. The statistics demonstrate that the average size of undissolved carbides is reduced from 14.19 μm to 0.63 μm, with a reduction percentage reaching 96%. Over the same duration, the number density of the undissolved carbides decreases from (0.19~0.55)/mm2 to (0.03~0.1)/mm2, and the percentage area of the undissolved carbides decreases from (1.26~1.68)% to (0~0.02)%. Thermodynamically, applying a pulsed magnetic field lowers the dissolution energy barrier of undissolved carbides and modifies their transformation temperature. Kinetically, the rate of alloy element diffusion is enhanced by increasing the frequency of atomic jumps. This research aims to provide new insights into enhancing the contact fatigue life of bearing steel, increasing the proportion of special steel, and optimizing the steel deep-processing process.